Digoxin lowers the incidence of prostate cancer: A nationwide population-based study. Issue 4 (April 2020) - Lin, Tzu-Ping; Fan, Yu-Hua; Chen, Yu-Chun; Huang, William J.S.
Abstract : Background: In vitro studies have confirmed that cardiac glycosides can induce apoptosis in both hormone-dependent and -independent prostate cancer (PCa) cell lines. The aim of this study was to investigate the incidence of PCa among patients treated with and without digoxin using a nationwide population-based database in Taiwan. Methods: We retrieved data of men aged 30 years or older who were newly diagnosed with heart failure between January 1998 and December 2003 from the National Health Insurance program database in Taiwan. We divided the patients into digoxin users and non-digoxin users. Kaplan-Meier curves and Cox proportional hazard analysis were used to examine the risk of subsequent PCa between the digoxin and non-digoxin groups. Results: The mean ± SD follow-up (years) periods in the digoxin and non-digoxin groups were 8.6 ± 1.78 and 8.3 ± 1.75, respectively. The cumulative incidence of PCa during the follow-up period was 3.5% (147/4233) in the non-digoxin group compared with 3.0% (65/2154) in the digoxin group. The log-rank test revealed that the digoxin group had a similar incidence of PCa to the non-digoxin group ( p = 0.18). After adjusting for age, benign prostatic hyperplasia, and comorbidities, Cox proportional hazard regression analysis showed that digoxin was associated with a significantly decreased risk of developing PCa (hazard ratio, 0.74; 95% CI, 0.548-0.993; p = 0.045). Moreover, logistic regression analysis showed that the risk of PCa decreased with a longer duration of digoxin use during the study period compared to those who had never used digoxin ( p = 0.043). Conclusion: The cardiac glycoside digoxin had significant effects on reducing the incidence of PCa in a time-dependent manner. Our findings may imply the potential application of cardiac glycosides in the prevention and management of PCa.